Harnessing Nature's Adjuvant: A Systematic Review and Meta Analysis of Phyllanthus niruri's Immunomodulatory and Chemosensitizing Mechanisms in Colorectal Cancer - Adhi Setradian Anto Maria; Albertus Ari Adrianto; Awal Prasetyo (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Colorectal cancer (CRC) poses a significant global health burden, and the limitations of conventional therapies necessitate the exploration of effective adjuvants. Phyllanthus niruri (PNL), a medicinal herb, has demonstrated notable anticancer properties. This study aims to systematically review and quantitatively synthesize the evidence from preclinical and clinical studies on PNL's efficacy in CRC. Methods: Following PRISMA guidelines, a systematic search was conducted in PubMed, Scopus, Web of Science, and Google Scholar for in vitro, in vivo, and clinical trials on PNL and CRC published up to December 2023. Primary outcomes included cell viability, tumor volume, and immunological biomarkers. Data were extracted for meta-analysis, calculating standardized mean differences (SMD) with 95% confidence intervals (CI) using a random-effects model to account for heterogeneity, which was assessed using the I² statistic. Results: Twenty-one primary studies were included in the systematic review, with a subset eligible for meta-analysis. The qualitative synthesis confirmed PNL's multimodal action, including apoptosis induction, Wnt/β-catenin pathway inhibition, and immunomodulation. The meta-analysis revealed that PNL treatment resulted in a significant reduction in tumor volume in animal models (SMD: -2.54; 95% CI: -3.87 to -1.21; p < 0.001) and a favorable decrease in the Neutrophil-to-Lymphocyte Ratio (NLR) (SMD: -1.89; 95% CI: -2.78 to -1.01; p < 0.001). Significant heterogeneity was observed across studies. Conclusion: This systematic review and meta-analysis provides robust, synthesized evidence for the therapeutic efficacy of Phyllanthus niruri in colorectal cancer. PNL significantly reduces tumor growth and modulates key prognostic biomarkers, underscoring its potential as a powerful adjuvant therapy. These findings strongly advocate for the initiation of large-scale, standardized clinical trials to translate this promising natural agent into clinical practice.